Hier & Après. (Montréal : Musée des Beaux-arts de Montréal, 1980)
Darboven, Hanne ; Fulton, Hamish ; Jonas, Joan ; Korot, Beryl ; Lewis, Glenn ; Massey, John ; Poirier, Anne & Patrick ; Acconci, Vito ; Aycock, Alice ; Becher, Bernd & Hilla ; Colette ; Gervais, Raymond ; Rinke, Klaus ; Sonnier, Keith
Hier & Après / Yesterday & After, Musée des Beaux-arts de Montréal, Volet I: 28 mars - 27 avril 1980 ; Volet II: 7 mai - 8 juin 1980
boek